Analisis Komprehensif Implementasi Kebijakan Ketahanan Pangan Berbasis Dana Desa di Indonesia Menurut Model Isi Kebijakan dan Lingkungan Implementasi Merilee S. Grindle - Sakir, Ahmad Rosandi; Silawane, Naifa Nabila (PENA BANGSA: Bisnis dan Tata Kelola Publik Adaptif, 2025)
Village Fund–based food security policy is a national priority expected to strengthen rural community food independence. However, its implementation demonstrates varying degrees of success across regions. This article aims to analyze the effectiveness of such policy implementation in Indonesia using Merilee S. Grindle’s model, which emphasizes the dimensions of content of policy and context of implementation. The study applies a Systematic Literature Review (SLR) approach to five scholarly articles published between 2023 and 2025 that are relevant to the topic. Article selection followed specific inclusion and exclusion criteria, and the findings were analyzed thematically using Grindle’s framework. The results indicate that successful implementation occurs when budget allocations are targeted correctly, program benefits align with local needs, and competent as well as responsive implementers are involved, as illustrated in Ciherang, Medaeng, and Tulikup. Conversely, failures arise from misallocation, weak institutional coordination, and the dominance of external actors neglecting community aspirations, as seen in Lamandau and Sukamukti. This synthesis confirms that the effectiveness of food security policy is not solely determined by policy design but also shaped by the interaction of interests, institutional capacity, and implementers’ responsiveness at the local level.